DIVORCE AND REMARRIAGE: An Approach to Biblical Theology - Margo Adi (Sekolah Tinggi Teologi Moriah, 2022)
Divorce and remarriage are issues that are not easily resolved. Differences in theological views on divorce and remarriage, as well as disagreements among local church leaders regarding divorce and remarriage as adultery, add to the uncertainty as well as the opportunities for divorce and remarriage. Based on that, this article aims to find and explain the problems of divorce and remarriage in Christianity. The research method used by the author is the study of biblical theology, which raises and analyzes biblical texts related to divorce and remarriage. The results of this study are the first, whatever the reason, divorce is not permitted. Second, remarriage is not permitted, however, if remarriage is considered a way, then remarriage can be carried out with strict and thorough pastoral conditions and care. Perceraian, dan pernikahan kembali merupakan persoalan yang tidak mudah diselesaikan. Perbedaan pandangan teologis tentang perceraian dan pernikahan kembali, serta ketidaksepahaman di antara para pemimpin gereja lokal dalam menyepakati sebuah perceraian sebagai dosa dan pernikahan kembali sebagai perzinaan, menambah ketidakpastian sekaligus peluang terjadinya perceraian dan pernikahan kembali. Berdasar hal itulah, artikel ini bertujuan menemukan dan menjelaskan persoalan perceraian dan pernikahan kembali dalam kekristenan. Metode penelitian yang digunakan penulis adalah kajian teologi biblis yang mengangkat dan menganalisa teks-teks Alkitab yang berkaitan dengan perceraian dan pernikahan kembali. Hasil penelitian ini adalah pertama apa pun alasannya perceraian tidak diizinkan. Kedua, pernikahan kembali tidak diizinkan, namun, jika pernikahan kembali dianggap sebagai jalan, maka dapat dilakukan pernikahan kembali dengan persyaratan dan pelayanan pastoral yang ketat dan teliti.